PENGARUH ISLAMIC MARKETING MIX TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA PELANGGAN MILENIAL SHOPEE - Mohamad Mondir (LP2M Universitas Ibrahimy, 2024)
This study aims to analyze and identify the impact of the Islamic marketing mix on customer loyalty, with customer satisfaction as a mediating variable. This research is a quantitative study with 159 samples of Shoppe millennial Muslim customers. This research uses random sampling and convenience sampling. The findings in this research show that the promotion of products, people, and places significantly affect customer satisfaction. Besides that, process, price, and physical evidence do not considerably affect customer satisfaction. Physical evidence, product, and promotion significantly affect customer loyalty, and variable people, price, place, process, and customer satisfaction do not substantially affect customer loyalty. Thus, it means promotion, physical evidence, price, process, people, product, and place can not be mediated by customer satisfaction on Shopee customer loyalty. This study has practical implications for people with online businesses who want to choose the right marketing strategy for creating customer satisfaction and loyalty in the Millennial era. This study could also be a reference for future researchers who will do Islamic marketing mix research by using the other variables and reset subjects.